2020
DOI: 10.1007/s00380-020-01648-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changes in body mass index after percutaneous coronary intervention on long-term outcomes in patients with coronary artery disease

Abstract: Little is known about the impact of changes in body mass index (BMI) after the percutaneous coronary intervention (PCI) on long-term outcomes in patients with coronary artery disease (CAD). Therefore, this study aimed to clarify this issue. We investigated data on CAD obtained from the SHINANO Registry, a prospective, observational, multicenter cohort study, from 2012 to 2013 in Nagano, Japan. One year after PCI, the enrolled patients were divided into the following three groups based on changes in BMI by tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…In a prospective multicenter study, patients who had undergone percutaneous coronary intervention were divided into three groups according to the changes of BMI. During a follow up of 4 years, patients with reduced BMI have a signi cantly higher risk of incident major adverse cardiac events than those with maintained or increased BMI, even after adjusting for confounders [14]. BMI uctuation and decrease were also associated with cardiovascular death in patients with myocardial infarction and left ventricular dysfunction or heart failure [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective multicenter study, patients who had undergone percutaneous coronary intervention were divided into three groups according to the changes of BMI. During a follow up of 4 years, patients with reduced BMI have a signi cantly higher risk of incident major adverse cardiac events than those with maintained or increased BMI, even after adjusting for confounders [14]. BMI uctuation and decrease were also associated with cardiovascular death in patients with myocardial infarction and left ventricular dysfunction or heart failure [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that purposeful weight loss in such patients may not be beneficial and may even be harmful. 4 , 10 , 29 , 30 We, and others previously, believe that there is no clear evidence that weight loss is beneficial after MI, especially in patients aged >75 years. 4 , 6 , 10 , 16 According to our findings, moderate weight loss should be recommended only for elderly people with obesity grade III.…”
Section: Discussionmentioning
confidence: 94%
“…Our results should be considered hypothesis-generating for future research, especially because we had no data on cardiorespiratory fitness and could not track data on long-term changes in BMI. 29 …”
Section: Discussionmentioning
confidence: 99%
“…A obesidade está diretamente associada ao aumento da mortalidade por doenças crônicas, dentre elas as doenças cardiovasculares, tendo grande importância como fator de risco para Doença Arterial Coronariana (DAC) . A elevação do IMC (>30 kg/m²) se mostrou como importante fator de risco para a ocorrência de IAM tendo como excessão indivíduos com obesidade metabólicamente saudável, que apresentaram resultados semelhantes a indivíduos com o IMC dentro da média considerada normal, porém esses casos foram raros visto que a maioria dos indivíduos obesos apresentaram distúrbios Em contrapartida, em doentes com doenças crônicas ou submetidos a intervenções cirúrgicas, tem -se percebido que a obesidade e o excesso de peso vêm sendo associados a menor taxa de Ainda, a mudança do peso corporal também f oi associada ao aumento da incidência de DCV, tanto a perda de peso quanto o aumento do peso f oram apontadas como f atores de mau p rognóstico nos casos de pacientes com DCV e Intervenção Coronária Percutânea, sendo a manutenção do peso corporal melhor do que o emagrecimento nesses casos, independente de obesidade e sobrepeso (LEE YB, et al, 2021;YUI H, et al, 2020).…”
Section: Discussionunclassified